2018
DOI: 10.7150/ijms.26186
|View full text |Cite
|
Sign up to set email alerts
|

Acid-electrolyzed functional water induces extracellular matrix metalloproteinase inducer, a possible novel alarmin, secretion from oral squamous cell carcinoma cell lines

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN) secretion was induced in the oral squamous cell carcinoma cell line HSC3 cell by acid-electrolyzed functional water (FW) stimulation. Augmented EMMPRIN secretion was not under transcriptional control; rather, it was derived from the intracellular storages. EMMPRIN secretion was also induced under oxidative stress and accompanied by the release of lactate dehydrogenase (LDH). The molecules released from cells undergoing necrosis are called as alarmins, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Recently, functional water has been used in many agricultural and medicinal applications [ 10 , 11 , 12 ]. In the present study, our findings indicated that terahertz-based functional mineral water was also toxic to the larvae and pupae of the three tested mosquito species in a concentration-dependent manner (0–333 ppm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, functional water has been used in many agricultural and medicinal applications [ 10 , 11 , 12 ]. In the present study, our findings indicated that terahertz-based functional mineral water was also toxic to the larvae and pupae of the three tested mosquito species in a concentration-dependent manner (0–333 ppm).…”
Section: Discussionmentioning
confidence: 99%
“…For example, guppies ( Poecilia reticulata ) are frequently introduced to both natural and artificial water bodies as biological control agents for mosquitoes [ 8 , 9 ]. Another example is functional water produced from plant-derived minerals, or acid electrolyzed water, which has proven useful in agricultural pest control and medicinal disinfection [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To explore the factors deeply involved in these effects, we generated a FW with several different characters in ongoing experiments, yet, no obvious factors have been identified so far. FW‐treated cells were found to release lactate dehydrogenase (LDH) into the culture media (Kusunoki et al, ). LDH is a cell damage marker, and the FW‐treated cells were expected to be damaged to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms have not been elucidated, these beneficial effects of FW might be attributed to increased cytokine release. Previously, we demonstrated that the treatment of several cell lines with FW resulted in the release of various factors 5 , 6 , 7 . Among them, the release of extracellular matrix metalloproteinase inducer (EMMPRIN) was significantly augmented in the human oral squamous cell carcinoma cell line (OSCC) HSC3 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that the treatment of several cell lines with FW resulted in the release of various factors 5 , 6 , 7 . Among them, the release of extracellular matrix metalloproteinase inducer (EMMPRIN) was significantly augmented in the human oral squamous cell carcinoma cell line (OSCC) HSC3 7 . Augmented EMMPRIN secretion was not regulated at the transcriptional level and appeared to be released from intracellular storage sites.…”
Section: Introductionmentioning
confidence: 99%